A Prospective Study of Posterior (Transpedicular) Approach versus Anterior (Transthoracic/Thoracoabdominal) Approach for Posttraumatic Compression Fracture of Thoracolumbar Vertebra in a Tertiary Care Center: Comparison of Clinical and Radiological Outcomes - Varshney, Rahul; Datta, Parthasarathi; Deb, Pulak; Ghosh, Santanu (Indian Journal of Neurotrauma, 2020)
Objective The aim of this article was to analyze the clinical and radiological outcomes of transpedicular decompression (posterior approach) and anterolateral approach in patients with traumatic thoracolumbar spinal injuries.Materials and Methods It was a prospective study of patients with fractures of dorsolumbar spine from December 2011 to December 2013. A total of 60 patients with traumatic spinal injuries were admitted during the study period (December 2011–2013), of which 51 cases were finally selected and taken for operations while 3 were eventually lost in follow-up. Twenty patients were operated by anterolateral approach, titanium mesh cage, and fixation with bicortical screws. Twenty-eight patients were treated with posterior approach and transpedicular screw fixation. Clinical and radiographic evaluations were performed on all 48 patients before and after surgery.Results There were 48 patients of thoracolumbar burst fractures with 40 male and 8 female patients. Range of follow-up was from 1 month to 20 months, with a mean of 7.4. Preoperatively in anterior group, 65% of the patients were bed ridden, 20% patients were able to walk with support, and 15% of the patients were able to walk without support. In posterior group, 78.57% patients were bed ridden, 10.71% were able to walk with support, and 10.71% patients were able to walk without support. Kyphotic angle changes were seen in 16 patients out of 18 in anterior group and 20 patients in posterior group out of 25. Out of 18 patients in anterior group, 14 showed reduction in kyphotic angle of 10 to 100 (improvement), with mean improvement of 4.070. In posterior group, 7 patients showed improvement of 10 to 80 (reduction in kyphotic angle) whereas 13 patients showed deterioration of 1 to 120. The mean improvement was 2.140 in 7 patients and mean deterioration was 4.920. No statistical difference was found (p > 0.05) regarding improvement in urinary incontinence during the follow-up period.Conclusion There are significant differences in anterior and posterior approaches in terms of clinical improvement. Compared with posterior approach, the anterolateral approach can reduce fusion segment and well maintain the kyphosis correction. The selection of treatment should be based on clinical and radiological findings, including neurological deficit.
Keywords: transthoracic; kyphosis; Cobb’s angle; titanium mesh; transthoracic